2015
DOI: 10.18514/mmn.2015.1325
|View full text |Cite
|
Sign up to set email alerts
|

A note on annihilators in distributive nearlattices

Abstract: In this note we propose a definition of relative annihilator in distributive nearlattices with greatest element different from that given in [6] and we present some new characterizations of the distributivity. Later, we study the class of normal and p-linear nearlattices, the lattice of filters and semi-homomorphisms that preserve annihilators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…In [3] it was shown that if A is a distributive nearlattice, then the set of all filters Fi(A) = Fi(A), ⊻, ⊼, →, {1}, A is a Heyting algebra, where the least element is {1}, the greatest element is A, G ⊻ H…”
Section: Theorem 2 ([2]mentioning
confidence: 99%
See 1 more Smart Citation
“…In [3] it was shown that if A is a distributive nearlattice, then the set of all filters Fi(A) = Fi(A), ⊻, ⊼, →, {1}, A is a Heyting algebra, where the least element is {1}, the greatest element is A, G ⊻ H…”
Section: Theorem 2 ([2]mentioning
confidence: 99%
“…The following definition given in [3] is an alternative definition of relative annihilator in distributive nearlattices different from that given in [10].…”
Section: Theorem 5 ([9]mentioning
confidence: 99%
“…In [3] the authors obtain new equivalences of distributivity of a nearlattice. In this section we present some new characterizations of distributivity using ideals, filters and the theory of relative annihilators.…”
Section: Some Equivalences Of Distributivitymentioning
confidence: 99%
“…The following definition given in [3] is an alternative definition of relative annihilators in distributive nearlattices different from that given in [10]. Let a ∈ A and F ∈ Fi(A).…”
Section: P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation